The Seismic Response of a Shallow Foundation Supported on Geogrid-Reinforced Sand Soil - Al-khafaji, Ruqayah; Shafiqu, Qassun S. Mohammed (Al-Nahrain Journal for Engineering Sciences, 2025)
Shallow foundation suffers from considerable settlement, displacement and tilting under earthquakes. This is particularly due to the shaking associated with earthquakes that lead to the generation of horizontal seismic load transferred through the soil to the foundation. Also, liquefaction could take place during the earthquake in the saturated loose sand. To alleviate the detrimental effect of earthquakes, ground improvement is required. This study examines the response of the shallow square foundation rested on loose sand soil reinforced with geogrid reinforcement when subjected to 2023 Turkey earthquake by using a shaking table system. Different number of geogrid layers are installed; (one, two, three and four), also various geogrid configurations were examined which are (straight, trapezoidal and reverse trapezoidal). The acceleration response, settlement, horizontal displacement, rotation and pore water pressure developed in the sand soil and the shallow foundation during 2023 Turkey earthquake has been examined. The settlement and the horizontal displacement, foundation rotation, acceleration and pore water pressure were measured using rope displacement transducers, tilt sensors, accelerometers and pore water transducers respectively. The results showed that the acceleration amplifies when passing through loose sand. The results also indicated that the shallow foundation experienced noticeable settlement, horizontal displacement and rotation when subjected to the seismic loads. On the other hand, the installation of geogrid proved to be effective in controlling the problems associated with earthquakes. The optimum geogrid reinforcement is occurred when three layers of geogrid placed in reverse trapezoidal configuration (3RT) since it gave the best reduction in the acceleration amplification and the highest decrease in the foundation settlement, displacement and tilting which is about (60-66) %. Nevertheless, the effectiveness of geogrid minimizes when the sand soil becomes saturated. In addition, liquefaction occurs during earthquakes especially at the shallower depths because of the decrease in the shear strength of saturated soil.